Evaluation of placebo fidelity and trial design methodology in placebo-controlled surgical trials of musculoskeletal conditions: a systematic review. Issue 4 (2nd April 2022) - Anderson, David B.; Beard, David J.; Sabet, Tamer; Eyles, Jillian P.; Harris, Ian A.; Adie, Sam; Buchbinder, Rachelle; Maher, Christopher G.; Ferreira, Manuela L.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: The number of placebo surgical trials on musculoskeletal conditions is increasing, but little is known about the quality of their design and methods. This review aimed to (1) assess the level of placebo fidelity (ie, degree to which the placebo control mimicked the index procedure) in placebo trials of musculoskeletal surgery, (2) describe the trials' methodological features using the adapted Applying Surgical Placebo in Randomised Evaluations (ASPIRE) checklist, and (3) describe each trial's characteristics. We searched 4 electronic databases from inception until February 18, 2021, for randomised trials of surgery that included a placebo control for any musculoskeletal condition. Protocols and full text were used to assess placebo fidelity (categorised as minimal, low, or high fidelity). The adapted 26-item ASPIRE checklist was also completed on each trial. PROSPERO registration number: CRD42021202131. A total of 30, 697 studies were identified in the search, and 22 placebo-controlled surgical trials of 2045 patients included. Thirteen trials (59%) included a high-fidelity placebo control, 7 (32%) used low fidelity, and 2 (9%) minimal fidelity. According to the ASPIRE checklist, included trials had good reporting of the "rationale and ethics" (68% overall) and "design" sections (42%), but few provided enough information on the "conduct" (13%) and "interpretation and translation" (11%) of the placebo trials. Most trials sufficiently reported their rationale and ethics, but interpretation and translation are areas for improvement, including greater stakeholder involvement. Most trials used a high-fidelity placebo procedure suggesting an emphasis on blinding and controlling for nonspecific effects.